PENDUGAAN CADANGAN KARBON TUMBUHAN BAWAH PADA KEMIRINGAN LAHAN YANG BERBEDA DI HUTAN PENDIDIKAN UNIVERSITAS SUMATERA UTARA KABUPATEN KARO - Sartika EC Siallagan; Muhdi Muhdi; Diana Sofia Hanafiah (Peronema Forestry Science Journal, 2016)
The purpose of this study were to determine the potential of carbon on under storey level and to determine the effect of slope on a large or small carbon stocks in understorey in education forest University of North Sumatera District Karo. The research was conducted in April 2015. Data was collected by using purposive sampling with random start. Plot size is 20m x 20m as 6 plots with 3 plots in area ramps and 3 plots in steep terrain. Data were collected by destructive methods. The results showed that 14 species are found under the ramps region and 12 species on the steep region. Potential carbon found in the ramps region that is equal to       93,08 kg/ha and the potential of the carbon contained in the steep region that is equal to 83,84 kg/ha. The carbon in the ramps region is larger than in the steep region. Keywords: carbon, understorey, ramps region, steep region, education forest University of North Sumatera